The Welfare State - Background, Achievements, Problems - Assar Lindbeck (Research Institute of Industrial Economics (IFN), 2006)
This paper starts out with a brief discussion of the historical background, the justifications and the political forces behind the built up of the modern welfare state. It also summarizes its major achievements in terms of economic efficiency and redistribution. The paper also tries to identify some major problems of contemporary welfare-state arrangements, differentiating exogenous shocks from endogenous behaviour adjustments by individuals to the welfare state itself. The latter include tax distortions, moral hazard, and endogenous changes in social norms concerning work and benefit dependency.
Keywords: H40; H53; H55; J22; 330; Justifications for Welfare State; Incentive Problems; Moral Hazard; Social Norms; Sozialstaat; Ökonomischer Anreiz; Moral Hazard; Öffentliche Güter; Soziale Sicherung; Gesetzliche Rentenversicherung; Arbeitsangebot